Immunological Demyelination Triggers Macrophage/Microglial Cells Activation without Inducing Astrogliosis - Frank Cloutier; Ilse Sears-Kraxberger; Krista Keachie; Hans S. Keirstead (Clinical and Developmental Immunology)
The glial scar formed by reactive astrocytes and axon growth inhibitors associated with myelin play important roles in the failure of axonal regeneration following central nervous system (CNS) injury. Our laboratory has previously demonstrated that immunological demyelination of the CNS facilitates regeneration of severed axons following spinal cord injury. In the present study, we evaluate whether immunological demyelination is accompanied with astrogliosis. We compared the astrogliosis and macrophage/microglial cell responses 7 days after either immunological demyelination or a stab injury to the dorsal funiculus. Both lesions induced a strong activated macrophage/microglial cells response which was significantly higher within regions of immunological demyelination. However, immunological demyelination regions were not accompanied by astrogliosis compared to stab injury that induced astrogliosis which extended several millimeters above and below the lesions, evidenced by astroglial hypertrophy, formation of a glial scar, and upregulation of intermediate filaments glial fibrillary acidic protein (GFAP). Moreover, a stab or a hemisection lesion directly within immunological demyelination regions did not induced astrogliosis within the immunological demyelination region. These results suggest that immunological demyelination creates a unique environment in which astrocytes do not form a glial scar and provides a unique model to understand the putative interaction between astrocytes and activated macrophage/microglial cells.